Emergence of Azole Resistance in Aspergillus - Wiederhold, Nathan P.; Patterson, Thomas F. (Seminars in Respiratory and Critical Care Medicine, 2015)
Resistance to the azole antifungals itraconazole, voriconazole, and posaconazole in Aspergillus species is a growing concern. This is especially alarming for A. fumigatus, where acquired resistance has been documented in patients with invasive disease caused by this species that were exposed to these agents, as well as in azole-naive individuals. The primary mechanisms of resistance that have been described in clinical strains include different point mutations in the CYP51A gene, which encodes the enzyme responsible for converting lanosterol to ergosterol via demethylation. Some resistant isolates also contain a tandem repeat in the promoter region of this gene that causes increased expression. These mutations, including TR34/L98H and TR46/Y121F/T289A have also been found in the environment in several areas of the world and have been demonstrated to cause resistance to azole fungicides used in agriculture, thus raising the concern of environmental spread of resistance. Treatment options are limited in patients with infections caused by azole-resistant isolates and include amphotericin B formulations or combination therapy involving an echinocandin. However, there are few clinical data available to help guide therapy, and infections caused by resistant A. fumigatus isolates have been reported to have high mortality rates.
Keywords: Aspergillus fumigatus; azole resistance; aspergillosis; voriconazole; itraconazole; posaconazole; CYP51A